2021
DOI: 10.3390/metabo11020128
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Metabolome Differences between C57BL/6 and DBA/2 Mouse Strains: Implications for Their Use as Models for Depression- and Anxiety-Like Phenotypes

Abstract: Mouse models are widely used to study behavioral phenotypes related to neuropsychiatric disorders. However, different mouse strains vary in their inherent behavioral and molecular characteristics, which needs to be taken into account depending on the nature of the study. Here, we performed a detailed behavioral and molecular comparison of C57BL/6 (B6) and DBA/2 (DBA) mice, two inbred strains commonly used in neuropsychiatric research. We analyzed anxiety-related and depression-like traits, quantified hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…C57BL/6Js are more prone to display depression-like profiles e.g. [25,42,43], although phenotypes may vary between laboratories e.g. [44], and greater IBA was observed in DBA/2Js in [45].…”
Section: Introductionmentioning
confidence: 99%
“…C57BL/6Js are more prone to display depression-like profiles e.g. [25,42,43], although phenotypes may vary between laboratories e.g. [44], and greater IBA was observed in DBA/2Js in [45].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a powerful approach to detect altered biosignatures in psychopathologies [39], which we have implemented to disentangle molecular profiles of neuropsychiatric phenotypes [40][41][42][43] as well as responses to pertinent therapeutic interventions [44][45][46][47][48][49][50]. Here, we used a targeted metabolomics platform to compare G72Tg and WT mice and identified lower nicotinate levels in G72Tg hippocampi.…”
Section: Discussionmentioning
confidence: 99%
“…Basal behavior among different mouse strains differs. In a comparative analysis of C57BL/6 and DBA/2 mice, we found that C57BL/6 mice are characterized by elevated depression-like and reduced anxiety-like behavior compared to DBA/2 mice [ 127 ]. Accordingly, the hippocampal and plasma metabolic metabolomic profiles were different between the two mouse strains.…”
Section: Perspectivesmentioning
confidence: 99%